Magnetic hardness of hexagonal and orthorhombic Fe3C, Co3C, (Fe–Co)3C, and their alloys with boron, nitrogen, and transition metals: A first-principles study - Justyn Snarski-Adamski; Mirosław Werwiński; Justyna Rychły-Gruszecka (APL Materials)
Restrictions on the availability of rare earth metals create a strong demand for new rare-earth-free hard magnetic materials. In this study, we considered a large set of materials that are closely related to orthorhombic Fe3C (cementite) with the aim of characterizing trends in their intrinsic magnetic properties, highlighting the relation between magnetic properties and the chemical composition, and identifying alloys that are optimal for applications. A comprehensive analysis was conducted on the full concentration ranges of hexagonal (ϵ) and orthorhombic (θ) phases of (Fe–Co)3C, (Fe–Co)3(B–C), (Fe–Co)3(C–N), and their alloys with 3d, 4d, and 5d transition metals. The calculations were performed using the density functional theory implemented in the full-potential local-orbital code. Calculated properties included formation energies, Curie temperatures, magnetic moments, magnetocrystalline anisotropy energies (MAEs), and magnetic hardnesses. The considered compositions exhibit a range of magnetic properties, including soft, semi-hard, and hard magnetic. The materials most promising for hard-magnetic applications are selected Co-rich orthorhombic and hexagonal (Fe, Co)3C alloys. The calculation results do not indicate that substituting with transition metals increases the potential of the alloys for permanent magnet applications. A significant drawback of alloying orthorhombic θ–Fe3C (cementite) with transition metals is the notable decline in the Curie temperature. Among the positive outcomes, we found that a considerable proportion of the orthorhombic Co3(B–C–N) alloys are magnetically hard, of which boron substitution raises the Curie temperature and improves stability. By mapping the dependence of MAE on the concentration of elements covering both the 3d (from Fe to Co) and 2p (from B, through C, to N) positions, we have demonstrated for the first time the near isoelectronic nature of MAE. The latter observation may be particularly useful in designing compositions of new magnetically hard materials.